An exploratory descriptive study of the sexual and reproductive health knowledge of postgraduate students at the University of Cape Town. - Mwamba, Bupe (Child Health Unit, 2019)
Globally and in South Africa, university students’ knowledge of sexual and reproductive health (SRH) is low. This study was conducted in response to the dearth of information about the sexual and reproductive health knowledge of postgraduate students. Research conducted to explore the SRH knowledge of undergraduate students suggests that the level of SRH knowledge among undergraduate students is low. The aim of this study was to determine the SRH knowledge of postgraduate students at University of Cape Town (UCT), in South Africa. A cross sectional survey design was utilized, using an adapted and pretested online questionnaire. All postgraduate students enrolled in the first semester of 2017 (9444) were invited to anonymously complete the online survey. Four hundred and six (406) students completed the online survey, of whom 293 were female and 107 males. The age range of respondents was between 18 years and 57 years, with the median age for both male and female respondents being 24 years. Six survey responses were excluded from the statistical analysis because of incomplete data. Post graduate students from the African continent comprised 90.75% of the respondents. Most respondents were white (51.50%) from both Africa and abroad. The results indicated that respondents knew about sexually transmitted infections, and human immunodeficiency virus (HIV) & acquired immune deficiency syndrome (AIDS). Female respondents were more aware of breast examination, and the role of Papanicolaou smear (Pap smear) in SRH. Almost half of the respondents in this study (49%) stated that they had no need for more information about contraceptives. Lecturers were identified as one of the top five sources of information across faculties, which could suggest that the university environment provides students with important SRH-related information. Most postgraduate students had knowledge of sexual and reproductive health with regards to contraception, Pap smear, clinical breast examination, STIs, HIV and AIDS. Further research should focus on the relationship between SRH knowledge and usage among this population. As university lecturers were identified as an important source of information across faculties, the University should consider the incorporation of SRH education in the broader curriculum and as an integral component of student health services.